2022
DOI: 10.21708/avb.2022.16.3.10821
|View full text |Cite
|
Sign up to set email alerts
|

Proximal composition, fatty acid profile, omegas and lipid quality in the tambaqui (Colossoma macropomum Cuvier, 1818) (Serrasalmidae) in “flatted cut”

Abstract: The aimed of this study was to determine proximal composition, fatty acid profile, omegas and lipid quality in the tambaqui (Colossoma macropomum) in “flatted cut”, produced and commercializeded by Rondônia state, Brazil. Three pieces of flatted tambaqui were collected from 40 fish weighing 1.10 ± 0.10 kg. Proximal composition were determined by AOAC Official method 969.23 and 968.08. The fatty acids were grouped to calculate ratio ∑PUFAs/∑SFAs and proportion ∑PUFAs (n-6/n-3),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Above all, the percentages of AA, eicosatrienoic acid (C20:3 n-6), and octadecadienoic acid (C18:2 n-6) can also be highlighted. They are fatty acids that help speed up the healing process and renew red cells and defense cells (Cavali et al, 2022b). These three PUFAs were found in the analyzed sections.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Above all, the percentages of AA, eicosatrienoic acid (C20:3 n-6), and octadecadienoic acid (C18:2 n-6) can also be highlighted. They are fatty acids that help speed up the healing process and renew red cells and defense cells (Cavali et al, 2022b). These three PUFAs were found in the analyzed sections.…”
Section: Discussionmentioning
confidence: 98%
“…However, the content and availability of fatty acids vary among fish species, depending on age and inclusion rates in the diet (Parthasarathy and Joseph, 2011;Petenuci et al, 2019). Tambaqui (C. macropomum) is an important source of animal protein and essential fatty acids for the Amazonian population, with the essential fatty acids such as EPA, DHA, AA, and ALA (Petenuci et al, 2019;Zhang et al, 2020;Cavali et al, 2022b). In addition, it is one of the highlighted species for cultivation in the North Region; as it originates from the Amazon River, it adapts to the conditions of the region and easily adapts to the growing environments (Porto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a market tendency to prefer younger fish, that is, the consumer market has preferred lighter fish. Dantas Cavali et al (2022a;2022c;2022d) found, in an attempt to verify the nutritional values of fish that are lighter than what is commonly commercialized, in order to reduce production costs by shortening/reducing the fattening period, that it is not necessary to complete the entire conventional production cycle. For example, pirarucu of 11.1 kg already meets the demand for nutritional values of the consumer market.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the demand for fish has intensified, due to the transmission of information related to its nutritional value and because its consumption adds to the health benefits and promotion of the population's quality of life (Cavali et al, 2022a;2022c). Scientific research around the world has revealed that fish consumption is associated with a low incidence of cardiovascular diseases, due to fact that fish has essential fatty acids, such as eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), α-linolenic acid (ALA), linoleic acid (AA), etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation